3D printed membrane‐integrated spacers for enhanced antifouling in ultrafiltration. Issue 42 (11th August 2022) - Khalil, Abdullah; Francis, Lijo; Hashaikeh, Raed; Hilal, Nidal
Abstract: Feed spacers are an important component of membrane‐based filtration systems as they promote turbulence and mass transfer during the filtration process—thereby, reducing the membrane fouling and improving the flux. Whereas spacers are used as a separate component in conjunction with membranes, herein, we demonstrate that membrane‐integrated spacers offer superior fouling resistance and hence an improved output flux during filtration. The integrated spacers were fabricated by 3D printing a composite slurry of UV curable resin and polyvinylidene fluoride on the Polyethersulfone‐based ultrafiltration (UF) membrane. After curing under the UV light, the 3D printed spacers showed excellent flexibility and mechanical integrity along with permanent adhesion to the UF membrane. When tested for filtration using humic acid as foulant, the integrated spacer offered significantly reduced fouling and an increased flux as compared with the commercial spacer. Moreover, it was found that the geometry of the integrated spacers plays an important role in their performance. Among different geometries, the "gyroid" geometry, with an optimal infill density, provided the highest fouling resistance while improving the flux by nearly 150% as compared with the commercial spacer. When tested as stand‐alone spacers, the 3D spacers with identical geometries resulted in an increased fouling and lower flux which confirmed the superior performance of membrane integrated spacers. Abstract :